Asymmetric Yttrium‐Catalyzed C(sp3)−H Addition of 2‐Methyl Azaarenes to Cyclopropenes - Luo, Yong; Teng, Huai‐Long; Nishiura, Masayoshi; Hou, Zhaomin (Angewandte Chemie International Edition, 2017)
An enantioselective C−H addition to a C=C bond represents the most atom‐efficient route for the construction of chiral carbon–carbon skeletons, a central research topic in organic synthesis. We herein report the enantioselective yttrium‐catalyzed C(sp3)−H bond addition of 2‐methyl azaarenes, such as 2‐methyl pyridines, to various substituted cyclopropenes and norbornenes. This process efficiently afforded a new family of chiral pyridylmethyl‐functionalized cyclopropane and norbornane derivatives in high yields and high enantioselectivities (up to 97 % ee). Enantioselective C(sp3)−H bond additions of 2‐methyl azaarenes, such as 2‐methylpyridines, to substituted cyclopropenes and norbornenes have been achieved by using a chiral half‐sandwich yttrium catalyst. This process afforded a series of chiral pyridylmethyl‐functionalized cyclopropane and norbornane derivatives in good yields, high enantioselectivity, and 100 % atom efficiency.